Shoreline Changed Analysis Due to the Sea Level Rise in Pariaman City West Sumatera Province - Khairunnisa, Nisrina; Mubarak, Mubarak; Galib, Musrifin (Journal of Coastal and Ocean Sciences, 2022)
This study was conducted along the coastal line of Pariaman City from February to May 2021 which aims to determine and mapping the changes of the coastal line due to sea level rise. Survey method with direct field observation were applied and satellite imageries were also used to find out the shoreline change of coast under study. Results showed that since 2001 to 2020 the mean sea level rise in Pariaman City were 2.01 cm/year. Predictions of sea level rise that will occur in 2025 and 2030 in sequence is 17.036 cm and 27.068, in addition the wide of missing area from 2020 to 2025 with an accumulation is around 3.74 ha and in 2025 to 2030 covering an area of 4.70 ha. The result to the year of 2025 occure to shift considerable coastline with average change of -9.03 m with the rate of the shoreline changed an average of -1.81 m/year. In the year 2030, shoreline changed with average change of -29.13 m with the rate of the shoreline changed an average of -5.83 m/year